COVID-19 vaccine-related adverse events following immunization in the WHO Western Pacific Region, 2021–2022 - Amarasinghe, Ananda; Cho, Heeyoun; Katalbas, Eve Rizza; Takashima, Yoshihiro (Western Pacific Surveillance and Response, 2023)
The speed at which new vaccines against coronavirus disease (COVID-19) were developed and rolled out as part of the global response to the pandemic was unprecedented. This report summarizes COVID-19 vaccine-related safety data in the World Health Organization Western Pacific Region. Data for 1 March 2021 to 31 March 2022 from 36 out of 37 countries and areas in the Western Pacific Region are presented. More than 732 million doses of eight COVID-19 vaccines were administered; reporting rates of adverse events following immunization (AEFIs) and serious AEFIs were 130.1 and 5.6 per 100 000 doses administered, respectively. Anaphylaxis, thrombosis with thrombocytopenia syndrome, and myocarditis/pericarditis were the most frequent COVID-19 adverse events of special interest (AESIs) reported. The reported rates of AESIs in the Western Pacific Region were within the range of expected or background rates. Vaccine benefits far outweigh the risk of reported serious adverse reactions and serious outcomes of COVID-19. Continued AEFI surveillance is recommended to better understand and ensure the safety profiles of novel COVID-19 vaccines.
Keywords: COVID-19 vaccines; safety; adverse drug event; Asia; Pacific Islands